Overcoming educational inequity for the urban poor through community-based schools: a case study of gajahwong school in Yogyakarta - Widyana, Rahma; Hriday, Bidta A. (Jurnal Konseling dan Pendidikan, 2024)
Education inequality in Indonesia, especially for the urban poor, remains a problem. The poor often do not have adequate access to quality education, which impacts on their opportunities to improve their lives. One approach that can address this issue is through community-based schools, which involve educators, volunteers with a keen interest in education, families and communities in the education process to create a more inclusive and contextualized learning environment. This research aims to explore and understand how Gajahwong School in Yogyakarta, Indonesia, a community-based school, seeks to address educational inequalities for children from poor urban communities. The main focus of this research is to examine the practices, principles and curriculum implemented in the school. This research used a qualitative case study approach to collect data on the implementation of community-based schooling at Gajahwong School. Data were collected through participatory observation and in-depth interviews with one community leader, two school administrators, two teachers and two classroom volunteers. Data collection was conducted for 12 months. The data analysis technique used is thematic analysis, while the research question studied is how the community-based school model at Gajahwong School facilitates children's rights to a good education in addressing educational inequality among children from the urban poor. Analysis also used N-Vivo to support qualitative data analysis. The findings report on  the practices, principles, and curriculum at Gajahwong School. Highlighting the urgency of inclusive and contextual education for children from poor urban communities, the school’s dynamic, contextual, and progressive curriculum is prepared for and based on the context of urban poor communities and children's rights, and is designed to meet children's needs and developmental characteristics. Inclusive and child rights-based education forms the basis of the curriculum which is designed in a thematic way, providing space for each child to develop according to his or her potential.